Balance in organizational structure - Zhang, Zhuozhi (2019)
In this work, graph theory and balance theory are utilized to denote and manage an organization. Within organizations or any establishments of human network, it is inevitable that interactions among people culminate into positive, negative or indifferent emotional polarity. Such interpersonal relationships can be expressed elegantly using signed graphs whereby the nodes represent individuals in an organization and the edges reflect the type of relationship among them. We derived techniques for reliably calculating the state of balance and implement computational algorithms of manageable time complexity to estimate the state of balance or imbalance of organizational structure based on established theorems on signed graphs. Accordingly, if a structure is balanced, it is usually beneficial to maintain status quo. Meanwhile, an imbalanced structure can serve as indications of improvement measures that can be taken by managers to avert any potential negative implications.